Log-Harmonic Mappings Associated With the Sine Function - Kumar, Sushil; ÇETİNKAYA, ASENA; Esra Özkan Uçar H. (Hacettepe University, 2025)
In this paper, we define new subclasses STlh (s) and CSTlh (s) of sine starlike log-harmonic mappings and sine close-to-starlike log-harmonic mappings, respectively, defined in the open unit disc D. We investigate representation theorem and integral representation theorem for functions in the class STlh (s). Further, we determine radius of starlikeness for functions in the classes STlh (s) and CSTlh (s).
Keywords: Radius of Starlikeness; Sine Close-to-starlike Log-harmonic Mapping; Sine Starlike Log-harmonic Mapping; Starlike Function